Understanding the Prophet's Hadith about Women with a Hermeneutic Approach: A Critical Study of Misogynistic Narrations - Muin, Firdaus; Ali Amiruddin, Andi Muhammad; Hayati, Salma; Fazil, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Misogynistic readings of hadith have significantly shaped gendered norms in segments of Muslim societies, contributing to restrictions on women’s leadership, religious authority, mobility, and marital agency. Such interpretations often rely on textual literalism detached from historical and socio-cultural contexts. This study critically re-examines selected hadiths frequently invoked to legitimize gender hierarchy through a hermeneutical framework. Adopting a qualitative design with a textual-analytical approach, the research analyzes narrations contained in the canonical collections of Muhammad al-Bukhari, Muslim ibn al-Hajjaj, Abu Dawud, Al-Tirmidhi, and Ibn Majah. The study integrates classical hadith scholarship with contemporary hermeneutical theory, emphasizing contextualization (asbāb al-wurūd), socio-historical analysis, and the ethical objectives (maqāṣid) underlying prophetic traditions. The findings demonstrate that many narrations commonly categorized as “misogynistic” are context-dependent and descriptive rather than universally prescriptive. Reports concerning women’s political leadership are shown to be situational (casuistic) responses to specific historical circumstances; narrations about a wife’s prostration signify moral respect rather than ontological subordination; traditions related to women leading congregational prayer admit interpretive plurality within juristic discourse; and reports restricting women’s travel without a mahram reflect concerns of security and social order in particular historical settings. Similarly, narrations regarding marital refusal are better understood as ethical exhortations promoting conjugal harmony rather than instruments of coercion. This study argues that a hermeneutically informed methodology offers a critical corrective to reductionist literalism in hadith interpretation. By situating prophetic traditions within their discursive and historical horizons while engaging contemporary ethical concerns, the approach contributes to a more equitable and context-responsive framework for gender discourse in Islamic studies.